Vibration exposure and biodynamic responses during whole-body vibration training - Abercromby, A. F. J.; Amonette, W. E.; Layne, C. S.; McFarlin, B. K.; Hinman, M. R.; Paloski, W. H. (Medicine & Science in Sports & Exercise, 2007)
Purpose: Excessive, chronic whole-body vibration (WBV) has a number of negative side effects on the human body, including disorders of the skeletal, digestive, reproductive, visual, and vestibular systems. Whole-body vibration training (WBVT) is intentional exposure to WBV to increase leg muscle strength, bone mineral density, health-related quality of life, and decrease back pain. The purpose of this study was to quantitatively evaluate vibration exposure and biodynamic responses during typical WBVT regimens.